Medium Access Control Protocols for Wireless Sensor Networks with Ambient Energy - Kosunalp, Selahattin; Tabakcıoğlu, Mehmet Barış (Ieee, 2016)
Wireless sensor networks (WSNs) have recently been a popular research area with a broad range of applications. One of the most significant constraints of WSNs is energy limitation of sensor nodes. Therefore, energy-efficiency has been considered as primarily design criterion in many medium access control (MAC) protocols developed. In order to solve the issue of limited-energy sources, various recent protocols have focused on energy harvesting from surrounding environment, such as solar, wind and vibration energy, resulting in providing unlimited energy source. Ambient energy exhibits a characteristic of unlimited energy source but not available always due to environmental changes. The focus is now being placed on effective utilization of the time-varying ambient energy. This study aims to provide a review of recently proposed MAC protocols for energy-harvesting WSNs describing their operating principles and underlying features.
24th Signal Processing and Communication Application Conference (SIU) -- MAY 16-19, 2016 -- Zonguldak, TURKEY
Keywords: wireless sensor networks; sensor node; ambient energy